Konsep Virtue Ethics dalam Pemikiran Syed Muhammad Naquib al-Attas dan Tantangan Postmodernisme - Dinar Dewi Kania (University of Darussalam Gontor, Indonesia, 2017)
In real life, Human being never be separated from ethics; A kind of topic that thediscussion will not be separated from good and evil. Because good and evil become the field of discussion, it will be closely related to human behavior or morals. Today’s problem, own morals, in post-modern times such as having missed directions. The values of good and evil, kind a look vague. Because of moral in this prespective; Good and evil is based on human reason an sich. This fact can not be separated from the influence of Western culture which removes the element of metaphysics in its moral ethics. Thus, Religion has no moral authority. So God and revelation have no place in their “framework.” This paper tries to explain some facts related to moral ethics. By presenting some explanations of how moral ethical discourse in the West, as well as presenting the concept of “Virtue Ethics” initiated by Syed Muhammad Naquib al-Attas.